Ontario Teachers’ Perceptions of the Controversial Update to Sexual Health and Human Development - Bialystok, Lauren (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
This article reports the findings of a web-based survey of Ontario health and physical education teachers conducted in 2017. The purpose of the study was to understand teachers’ views of the aims of the 2015 revised “sex ed” curriculum and the public debate that surrounded it, as well as to explore their own values around the teaching of sexuality. The respondents overwhelmingly supported the curriculum, expressed liberal values that included respect and inclusion, and called for more education to integrate comprehensive sexuality education into the school system. The findings are relevant to ongoing political battles focused on education in Ontario and across Canada.